Long-term safety of dexamethasone sodium phosphate encapsulated in autologous erythrocytes in pediatric patients with ataxia telangiectasia - Koenig, Mary Kay; Leuzzi, Vincenzo; Gouider, Riadh; Yiu, Eppie M.; Pietrucha, Barbara; Stray-Pedersen, Asbjørg; Perlman, Susan L.; Wu, Steve; Burgers, Trudy; Borgohain, Rupam; Kandadai, Rukmini Mridula; Meyts, Isabelle; et al. (Frontiers in Neurology, 2025)
BackgroundDexamethasone sodium phosphate (DSP) encapsulated in autologous erythrocytes (EryDex) was developed as an alternative to standard glucocorticoids in an effort to eliminate chronic steroid toxicity while preserving efficacy. The primary objective of this report is to describe the safety of long-term use of EryDex in treatment of pediatric patients with ataxia telangiectasia.MethodsThis is a post-hoc analysis of patients treated with EryDex for a minimum of 24 months in two prospective clinical trials. Outcomes include adverse events, growth, hemoglobin and serum iron, glucose levels, HbA1c, CD4+ lymphocytes, and bone mineral density.ResultsSixty-eight patients completed a minimum of 2 years of treatment with EryDex (mean treatment length 39 ± 11 months). Treatment-emergent adverse events (TEAE), reported in 67 (99%) out of 68 patients, were typically mild and did not cause discontinuation of treatment or death. Treatment-related TEAE were noted in 48 (71%) patients. Notable adverse events included transient pruritus reported in 23 (34%) patients and findings of low serum iron reported in 27 (40%) patients, while at baseline one fifth of patients had low serum iron. Anemia was reported in 9 (13%) patients. The mean hemoglobin level changed by −0.8 ± 1.0 g/dL after 6 months of therapy without subsequent decline. Longitudinal height and weight mean z-scores showed minimal change from baseline to month 24 for height (−0.06 ± 0.49), weight (−0.02 ± 0.71), and body mass index (0.03 ± 0.87). The mean bone mineral density (BMD) z-score showed a decline of 0.4 points over the 24 months of treatment. Values for glucose, HbA1c, cortisol, and CD4+ lymphocyte counts did not show clinically significant changes during prolonged treatment with EryDex.ConclusionThe most common treatment-related adverse events were transient infusion-related pruritus and iron deficiency. There was a decline in BMD which could not be distinguished from the natural course of disease. There were no adverse effects on height, weight and body mass index noted, as documented by stable z-scores throughout the 2 years of treatment. Adverse events typically observed with prolonged glucocorticoid use such as Cushingoid features, weight gain, hypertension, hirsutism, diabetes or stunted growth were rarely reported.Clinical trial registrationClinicalTrials.gov, identifiers: NCT02770807 and NCT03563053.